Memutus Rantai Kemiskinan: Upaya Pemerintah Merehabilitasi Gelandangan dan Pengemis - Rahmatullah Rahmatullah; Marwan Djafar; Nur Insani (Jurnal Litigasi Amsir, 2024)
This study analyzes the strategy of the Gorontalo City Government in dealing with homeless people and beggars based on Peraturan Daerah No. 1 Tahun 2018 tentang Ketertiban Umum. This study uses qualitative methods to evaluate the effectiveness of policy implementation, barriers, and impacts. The results show that despite active efforts, the effectiveness of control still needs to be improved due to constraints such as lack of resources and public awareness. Control has succeeded in reducing the number of homeless people and beggars in some public areas, but long-term solutions still need to be strengthened. Inhibiting factors include a lack of coordination between agencies, limited rehabilitation facilities, and community response.